Normally-off fully recess-gated GaN metal–insulator–semiconductor field-effect transistor using Al2O3/Si3N4 bilayer as gate dielectrics. (28th September 2017) - Wang, Hongyue; Wang, Jinyan; Liu, Jingqian; Li, Mengjun; He, Yandong; Wang, Maojun; Yu, Min; Wu, Wengang; Zhou, Yang; Dai, Gang
Abstract: By a self-terminating gate recess etching technique, a normally-off fully recess-gated GaN metal–insulator–semiconductor field-effect transistor (MISFET) was fabricated using Al2 O3 /Si3 N4 bilayer as gate dielectrics. Owing to the high breakdown electric field (∼10 MV/cm) of the gate dielectrics, the device exhibits a large gate swing of 18 V, a high threshold voltage of 1.7 V (at I D = 100 µA/mm), a large maximum drain current of 534 mA/mm, a gate leakage current lower than 20 nA/mm in the whole gate swing, and a high OFF-state breakdown voltage of 1282 V. Furthermore, owing to the high gate overdrive ( V GS − V TH ), the on-resistance of the device only increases by 5.4% under a constant stress of V GS / V DS = 18 V/1 V.